2016
DOI: 10.1111/afe.12186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the emerald ash borer invasion on the community composition of arthropods associated with ash tree boles in Maryland, U.S.A.

Abstract: Emerald ash borer (EAB) Agrilus planipennis Fairmaire is an invasive non‐native woodboring beetle that has killed hundreds of millions of ash trees (Fraxinus spp.) in North America. Identifying the arthropod community associated with ash trees has been highlighted as an important research requirement in understanding the wider effects of EAB. We harvested live ash trees infested with EAB at 37 sites in Maryland from 2011 to 2014 and collected a total of 2031 arthropods. All arthropods were identified to order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Parasitism was only detected at sites within Prince George's County, MD. Interestingly, the only other O. agrili recovered in Maryland in a separate study was also in Prince George's County [9]. All of the adult parasitoids that emerged in the present study were identified as O. agrili.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Parasitism was only detected at sites within Prince George's County, MD. Interestingly, the only other O. agrili recovered in Maryland in a separate study was also in Prince George's County [9]. All of the adult parasitoids that emerged in the present study were identified as O. agrili.…”
Section: Discussionsupporting
confidence: 50%
“…Of the invasive woodboring insects in the USA, emerald ash borer (EAB), Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) is especially damaging [6][7][8][9][10]. EAB is native to northeastern Asia and is thought to have been accidentally introduced to North America sometime in the 1990s [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Field surveys of non-target insects associated with ash trees following field releases of introduced EAB parasitoids in Michigan and Maryland found no evidence of non-target attack from these introduced parasitoids [45]. In contrast, arthropod diversity associated with ash trees is significantly reduced because of the EAB invasion in Maryland [78]. The parasitoids introduced from Asia were selected for high EAB-host specificity, and in the aftermath of the EAB invasion of North America, the resulting conservation of Fraxinus and recovery of forests will produce many desirable ecological benefits [79,80].…”
Section: Development Of An Eab Biological Control Program In North Ammentioning
confidence: 97%
“…reasonably [78]. The parasitoids introduced from Asia were selected for high EAB-host specificity, and in the aftermath of the EAB invasion of North America, the resulting conservation of Fraxinus and recovery of forests will produce many desirable ecological benefits [79,80].…”
Section: Introduction and Establishment Of Eab Biocontrol Agentsmentioning
confidence: 99%
“…The loss or reduction of ash in North America will permanently alter forest ecosystems wherever ash represents a significant fraction of tree community composition, and many species that are dependent on ash are likely to be affected. For example, at least 44 species of arthropods within the current range of EAB are known to feed only on ash, including 24 lepidopterans and a number of coleopterans, and are now considered at risk should ash become rare or locally extinct [18][19][20].…”
Section: Introductionmentioning
confidence: 99%